Preparation of Male Meiotic Chromosomes for Fluorescence In Situ Hybridization and Immunodetection with Major Focus on Dogroses - Lunerová, Jana; Vozárová, Radka (Methods in molecular biology (Clifton, N.J.), 2023)
Meiosis is a very essential cell division resulting in the formation of four haploid gametes in plants. The preparation of meiotic chromosomes is a key step in plant meiotic research. Well-spread chromosomes, low background signal, and effective cell wall elimination give the best hybridization results. Dogroses (Rosa, section Caninae) are allopolyploids and frequently pentaploids (2n = 5x = 35) with asymmetrical meiosis. Their cytoplasm is enriched with organic compounds such as vitamins, tannins, phenols, essential oils, and many more. The cytoplasm is often a huge problem, avoiding successful cytogenetic experiments using fluorescence staining techniques. Here, we present a protocol with modifications for the preparation of male meiotic chromosomes suitable for fluorescence in situ hybridization (FISH) and immunolabeling with a major focus on dogroses.
Keywords: Flower buds; Immunodetection; Rosa; In Situ Hybridization, Fluorescence; FISH; meióza; zárodečné buňky; Polyploidy; Germ Cells; Chromosome preparation; lidé; Meiosis; chromozomy; Chromosomes; Asymmetrical meiosis; Humans; hybridizace in situ fluorescenční; polyploidie